2023
DOI: 10.1002/vetr.3308
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactive carbohydrate determinants in atopic and healthy dogs and their influence on allergy test specificity

Bettina Kasper,
Teresa Boehm,
Nadine Wittenstein
et al.

Abstract: BackgroundThe selection of allergens for immunotherapy in atopic dogs is often based on serum allergy testing. Cross‐reactive carbohydrate determinants (CCDs) are common structures in plant and insect allergens that reportedly induce polysensitisation, reduce agreement between intradermal and serum tests and complicate allergen selection.MethodsThirty‐four dogs with diagnosed atopic dermatitis and 10 healthy dogs were included in the study. An intradermal test was conducted in atopic dogs, and serum samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, interestingly, non-atopic dogs did not present with anti-CCD IgE. 5 This contrasts with work by Piccione and colleagues, which reported that 13 per cent of non-atopic dogs had such antibodies, although titres were much lower than observed in atopic dogs. 9 Given the findings of this and previous studies, it is clear that we must now apply a new lens when looking back over the literature examining the prevalence of allergen-specific IgE in atopic and non-atopic animals -that of whether testing was performed before or after anti-CCD IgE antibody blocking.…”
Section: What You Need To Knowmentioning
confidence: 75%
See 4 more Smart Citations
“…However, interestingly, non-atopic dogs did not present with anti-CCD IgE. 5 This contrasts with work by Piccione and colleagues, which reported that 13 per cent of non-atopic dogs had such antibodies, although titres were much lower than observed in atopic dogs. 9 Given the findings of this and previous studies, it is clear that we must now apply a new lens when looking back over the literature examining the prevalence of allergen-specific IgE in atopic and non-atopic animals -that of whether testing was performed before or after anti-CCD IgE antibody blocking.…”
Section: What You Need To Knowmentioning
confidence: 75%
“…However, despite the possible methodological explanations for the discrepancies between serum and intradermal test results, the view that CCD-specific IgE causes false positive reactions in ELISA-based serum allergy testing has prevailed, and diagnostic laboratories are increasingly using anti-CCD IgE blockers before processing ELISA samples. 4 In a study summarised on p 410 of this issue of Vet Record, 5 Kasper and colleagues explored the concept further by comparing the results of intradermal and serum testing in a group of 34 dogs with atopic dermatitis. As reported in previous studies, [6][7][8] the correlation between the intradermal and serum test results was relatively poor.…”
Section: Blocking Cross-reactive Carbohydrate Determinant-specific Ig...mentioning
confidence: 99%
See 3 more Smart Citations